2016
DOI: 10.12968/jowc.2016.25.5.232
|View full text |Cite
|
Sign up to set email alerts
|

Surgical wound assessment and documentation of nurses: an integrative review

Abstract: The authors declare that they have no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
4
25
0
4
Order By: Relevance
“…The findings from this study stress the need to develop interventions that are designed to standardise documentation practices in this hospital, a finding consistent with evidence from current literature (Ding et al, ). Understandably, clear and complete wound care documentation helps healthcare professionals to communicate and track patients’ wound healing process.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings from this study stress the need to develop interventions that are designed to standardise documentation practices in this hospital, a finding consistent with evidence from current literature (Ding et al, ). Understandably, clear and complete wound care documentation helps healthcare professionals to communicate and track patients’ wound healing process.…”
Section: Discussionsupporting
confidence: 89%
“…Marshall, West, and Aitken (2013) reported that nurses often used their peers as source of knowledge. A recent integrative review identified very few studies which investigated wound documentation practices, but where documentation was reported, it was often described as incomplete or inconsistent (Ding, Lin, & Gillespie, 2016;Gillespie, Chaboyer, Kang et al, 2014). These findings highlight the need to explore why there is limited adherence to wound care CPGs in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to describe, through observations, nurses' surgical wound practices in an acute university hospital in Australia. To the best of our knowledge, 27 this study is the first to examine nurses' practices prospectively, and thus provides a baseline for further research in this area. The results of this study suggest that there are some incongruencies in the uptake of guidelines on aseptic technique in surgical wound care.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no audit tool is available and no cross-sectional observational study has been conducted on nurses' management of surgical wounds healing by primary intention. 27…”
mentioning
confidence: 99%
“…Further studies are needed, however, to understand how nursing documentation and patient/family education may be improved in local practice (Ding et al. ). Quality documentation is imperative as it facilitates the nursing process and enables effective communication between healthcare professionals (Ousey & Cook ).…”
Section: Discussionmentioning
confidence: 99%